Sustainable charcoal production from rubber tree branches (Hevea brasiliensis) - Sairod Suriyan; Jiamrittiwong Prayut; Puangngernmak Nutdechatorn (E3S Web of Conferences)
Dwindling firewood supplies for charcoal production necessitate exploration of alternative sources. Agricultural residues, particularly abundant rubber tree branches, present a promising solution. To evaluate their viability, a study employed a 200-liter charcoal retort kiln with wood gas circulation to carbonize rubber tree branches. The resultant charcoal underwent analysis for moisture content, fixed carbon, volatile matter, ash content, and higher heating value. The findings revealed a 6-hour carbonization process with a peak temperature of 600°C. The produced charcoal displayed favorable properties: 4.78±0.53% moisture content, 11.46±0.99% volatile matter, 6.03±0.22 ash content, 77.73±0.42% fixed carbon, and a higher heating value of 30.97±0.50 MJ/kg. Notably, rubber tree branch charcoal surpassed bamboo, coconut shell, and commercially available options in higher heating value, signifying its potential as a sustainable alternative. Furthermore, it complies with Thai Community Product Standards for wood charcoal used for cooking. These results underscore the promising potential of rubber branches as a sustainable charcoal feedstock, addressing the critical issue of firewood scarcity through waste repurposing.